How urban welfare affects the hukou selection of rural migrants that belong to dual-hukou families in china - Chen Lu; Jian Chen; Jiewei Li; Xuetong Wang (Comparative Migration Studies, 2025)
Abstract Despite the Chinese government’s implementation of numerous policies aimed at promoting urbanization, the actual urbanization rate has not met expectations. Even when some rural migrants are presented with opportunities to convert to urban-hukou status, an increasing number of families opt to maintain a dual-hukou arrangement (where one spouse holds rural-hukou and the other holds urban-hukou). This phenomenon has garnered significant attention; however, the impact of diverse access to urban welfare on migrants’ hukou selection has been underexplored in existing research on hukou conversion. Access to urban welfare emerges as a critical factor influencing hukou selection decisions. This study constructs an analytical framework to examine the hukou arrangements of dual-hukou families, exploring the effects of various factors related to urban welfare acquisition on the hukou selection of rural migrants. Empirical results indicate that within dual-hukou families, migrants with rural-hukou status can obtain urban welfare through family support or market purchases. Consequently, to maximize family benefits, they prefer to retain their rural-hukou status rather than convert to urban-hukou. Conversely, possession of a qualification certificate from the host city negatively impacts rural-hukou retention. Additionally, rural migrants in dual-hukou families tend to favor cities with high-value hukou and express a desire to convert to local hukou status. These findings offer robust insights for policymaking, demonstrating resilience against sample self-selection bias and reverse causality.